The Use of Video Games as a Teaching Tool to Improve Teaching-Learning: State of the Art Review - Roncancio-Ortiz, Angie Paola; Ortiz-Carrera, Marco Fidel; Llano-Ruiz, Humberto; Malpica-López, Magally Jhoanna; Bocanegra-García, Jose Joaquin (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
In this new era of the 21st century when societies are constantly changing, education is the cornerstone to provide the people not only with the basic knowledge and tools, but also with the required skills for facing the challenges in a globalized world. Thus, video games have evolved from distractive activities, to more valuable tools. These tools can play a leading role in education-related processes, for example, supporting teaching tasks. The aim of this article is to present a state of art review on several particular experiences in which video games have been incorporated into teaching and learning activities. As a result, video games can be used as didactic mechanisms that help students, among other things, to solve learning problems, to improve motor and cognitive skills, and to foster creativity.